2019
DOI: 10.1021/acs.molpharmaceut.9b00571
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Delivery of the Peptide Agonist Specific to Neuromedin-U Receptor 2 to the Brain for the Treatment of Obesity

Abstract: Obesity and metabolic syndrome are threats to the health of large population worldwide as they are associated with high mortality, mainly linked to cardiovascular diseases. Recently, CPN-116 (CPN), which is an agonist peptide specific to neuromedin-U receptor 2 (NMUR2) that is expressed predominantly in the brain, has been developed as a new therapeutic candidate for the treatment of obesity and metabolic syndrome. However, treatment with CPN poses a challenge due to the limited delivery of CPN to the brain. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Both receptor subtypes are closely related to the regulation of food intake and energy balance. Peripheral and central administration of NMU reduced food intake and weight gain by stimulating NMUR1 and NMUR2, respectively 10 12 . Compared with the NMUR1-selective agonist, the NMUR2 selective agonist has a more potent body weight-lost effect and cause less diarrhea, making it a more well-balanced drug for the treatment of obesity 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Both receptor subtypes are closely related to the regulation of food intake and energy balance. Peripheral and central administration of NMU reduced food intake and weight gain by stimulating NMUR1 and NMUR2, respectively 10 12 . Compared with the NMUR1-selective agonist, the NMUR2 selective agonist has a more potent body weight-lost effect and cause less diarrhea, making it a more well-balanced drug for the treatment of obesity 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported on direct drug delivery to the brain via nasal application. Our previous articles have clarified the efficient nasal delivery of oxytocin and CPN‐116 (the agonist peptide of type 2 neuromedin U receptor) to the brain 22,23 . Nasal application of ANA‐TA9 may allow for the development of novel therapeutic systems to treat AD and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…There are two known, parallel mechanisms of transnasal drug transport into the brain: (1) straight influx into the cerebrospinal fluid (CSF) via epithelial cell layer and submucosa and/or entry to neuropilus using extracellular diffusion within perineuronal spaces; (2) intracellular transmission of the pharmaceutical molecules across the olfactory neurons to cortical areas (Borroto‐Escuela et al, 2015). Of note, the exchange of molecules between two parts of the recently described glymphatic system: CSF and brain extracellular fluid (BECF) may also facilitate the efficient central distribution of intranasally delivered medications (Tanaka et al, 2020, Figure 1).…”
Section: Pharmacological Perspectives Of Intranasal Nmur2 Agonists Ap...mentioning
confidence: 99%